Trajno ohranjanje digitalnih virov - Kavčič-Čolić, Alenka (Knjižnica, 2010)
The paper is a review of digital preservation theory and practice. Main concepts, standards and recommendations in this field as well methods implemented by digital archives (libraries and archival institutions responsible for digital preservation) are presented. Although digital preservation is still evolving and we do not know whether the selected methods are reliable, it is generally known that implementing any method with consistency, we can considerably contribute to the preservation of the access to the archived digital contents.
Keywords: knjižnice; knjižnično gradivo; digitalizacija; digitization; digitalni viri; trajno ohranjanje; koncepti; metode; standardi